Adventitious rooting declines with the vegetative to reproductive switch and involves a changed auxin homeostasis - Rasmussen, Amanda; Hosseini, Seyed Abdollah; Hajirezaei, Mohammed-Reza; Druege, Uwe; Geelen, Danny (Oxford University Press, 2015)
Adventitious rooting, whereby roots form from non-root tissues, is critical to the forestry and horticultural industries that depend on propagating plants from cuttings. A major problem is that age of the tissue affects the ability of the cutting to form adventitious roots. Here, a model system has been developed using Pisum sativum to differentiate between different interpretations of ageing. It is shown that the decline in adventitious rooting is linked to the ontogenetic switch from vegetative to floral and is mainly attributed to the cutting base. Using rms mutants it is demonstrated that the decline is not a result of increased strigolactones inhibiting adventitious root formation. Monitoring endogenous levels of a range of other hormones including a range of cytokinins in the rooting zone revealed that a peak in jasmonic acid is delayed in cuttings from floral plants. Additionally, there is an early peak in indole-3-acetic acid levels 6h post excision in cuttings from vegetative plants, which is absent in cuttings from floral plants. These results were confirmed using DR5:GUS expression. Exogenous supplementation of young cuttings with either jasmonic acid or indole-3-acetic acid promoted adventitious rooting, but neither of these hormones was able to promote adventitious rooting in mature cuttings. DR5:GUS expression was observed to increase in juvenile cuttings with increasing auxin treatment but not in the mature cuttings. Therefore, it seems the vegetative to floral ontogenetic switch involves an alteration in the tissue’s auxin homeostasis that significantly reduces the indole-3-acetic acid pool and ultimately results in a decline in adventitious root formation.